Detection of IgM, IgG and SARS-CoV-2 RNA among the personnel of the University of Milan, March through May 2020: the UNICORN study. Issue 3 (24th March 2021) - Milani, Gregorio Paolo; Rota, Federica; Favero, Chiara; Dioni, Laura; Manenti, Alessandro; Hoxha, Mirjam; Pariani, Elena; Albetti, Benedetta; Pesatori, Angela Cecilia; Montomoli, Emanuele; Bollati, Valentina
Abstract : Objectives: In Italy, the pandemic of COVID-19 resulted in congestion of hospitals and laboratories and probably determined an underestimation of the number of infected subjects, as the molecular diagnosis of SARS-CoV-2 infection was mainly performed on hospitalised patients. Therefore, limited data are available about the number of asymptomatic/paucisymptomatic subjects in the general population across time. To understand SARS-CoV-2 infection in the general population, we have developed a cross-sectional study (the 'UNIversity against CORoNavirus study') to investigate infection trends in asymptomatic/paucisymptomatic subjects in Milan (Italy), between March and June 2020. Participants: The study population included 2023 subjects asymptomatic at the enrolment. Primary outcome measures: A nasal mid-turbinate swab for the detection of SARS-CoV-2 RNA and blood specimen for testing serum antibodies (immunoglobulin M (IgM) and IgG) were collected. Results: Subjects showing positivity for the SARS-CoV-2 RNA and/or for anti-SARS-CoV-2 Ig is 237 (11.7%). Only 1.2% (n=25) of the total population had a positive nasal swab for SARS-CoV-2 and the large majority (21/25) of them were observed in March. A total of 226 subjects (11%) had IgM (n=19; 0.9%), IgG (n=155; 7.7%) or both (n=52; 2.6%) against SARS-CoV-2. Subjects with a present or past SARS-CoV-2 infection did not differ from other subjects as regards the number of cohabiting family members, travels, fever and upper and lower respiratory infection episodes. Conclusions: Results from the present study support the hypothesis that the actual spread of the virus in Lombardy was underestimated in the official records. However, as it is not known how long Ig persist, numbers should be taken cautiously.